Curcuminoids can prevent post-contrast acute kidney injury in chronic kidney disease patients: A randomized controlled trial. Issue 39 (30th September 2022) - Jaturapisanukul, Solos; Kurathong, Sathit; Ngamvichchukorn, Tanun; Trakarnvanich, Thananda
Abstract : Background: Post contrast acute kidney injury (PC-AKI) following coronary procedures is a common cause of renal impairment in hospitalized patients, curcuminoids exert anti-inflammatory and antioxidant actions and have shown positive effects on renal hemodynamic protection The objective of this study was to evaluate the role of curcuminoids in the prevention of PC-AKI in chronic kidney disease (CKD) patients. Methods: This study was a single-center, prospective, double-blind, randomized, placebo-controlled trial in patients with CKD undergoing elective coronary angiography (CAG) at Vajira Hospital from October 2018 to March 2019. Patients were randomized to receive curcuminoids at 1500 mg per day 3 days before and 2 days after the procedure or placebo. The primary outcome was the development of PC-AKI, and the secondary outcomes were overall acute kidney injury (AKI) incidence within 7 days after CAG, changes in estimated glomerular filtration rate (eGFR), interleukin-6 (IL-6), high sensitivity C-reactive protein (hs-CRP), and other adverse events. Results: Sixty patients were enrolled in this study (30 in the curcuminoid group and 30 in the control group). AKI developed in 5 patients in the control group but not in the curcuminoid group (16.67% vs 0%, P  = .052). that curcuminoids could preserve changes in eGFR compared to the placebo group (-1.5 vs 2.5 mL/min/1.73 m 2, P value <.001 within 48 hours and -4 vs 1 mL/min/1.73 m 2, P value 0.002 within 7 days). However, the hs-CRP and IL-6 levels did not differ between the groups. No serious adverse events were observed in either of the groups. Conclusion: Prophylactic administration of curcuminoids, in addition to standard treatment, reduces the incidence of PC-AKI in patients with CKD undergoing elective CAG.